2011
DOI: 10.1097/mbc.0b013e328345f582
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk factors

Abstract: With increasing longevity, the prevalence of cardiovascular disease (CVD) risk factors in hemophilia patients is expected to increase; however, evidence-based guidelines on management are lacking. The aim of the study was to determine the prevalence and management of CVD risk factors in hemophilia patients. A retrospective study of 58 adult hemophilia patients (≥35 years) attending Mayo Comprehensive Hemophilia Center between 1 January 2006 and 15 October 2009 were reviewed. The prevalence of CVD risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…14 In their study of a US population aged more than 35 years old with hemophilia, Lim and Pruthi found that the prevalence rates of hypertension and diabetes were 65.5% and 10.3%, respectively. 7 The prevalence rates of diabetes and hypertension in the current study (1.3% and 0.2%, respectively) were less than that reported in other studies, which may be due to the younger population of study (mostly below 40 years of age).…”
Section: Discussioncontrasting
confidence: 52%
“…14 In their study of a US population aged more than 35 years old with hemophilia, Lim and Pruthi found that the prevalence rates of hypertension and diabetes were 65.5% and 10.3%, respectively. 7 The prevalence rates of diabetes and hypertension in the current study (1.3% and 0.2%, respectively) were less than that reported in other studies, which may be due to the younger population of study (mostly below 40 years of age).…”
Section: Discussioncontrasting
confidence: 52%
“…PWH are susceptible to the same cardiovascular risk factors as individuals without hemophilia, and even more so to certain traditional risk factors such as hypertension 15 , 24 26 and obesity related to limited mobility from arthropathy. 18 , 27 In a cohort of more than 700 PWH from the Netherlands and United Kingdom, the predicted 10-year risk of fatal MI or stroke was significantly higher (8.9%) than in the general population (6.7%), based solely on typical factors determining cardiovascular risk (including age, blood pressure, total/high-density lipoprotein cholesterol, body mass index, and smoking or DM history).…”
Section: Underlying Disease Course Life Expectancy and Age-related mentioning
confidence: 99%
“…Data suggest that screening and intervention for these traditional risk factors are currently suboptimal in PWH. 26 Aggressive management of individual cardiovascular risk factors with appropriate medications and lifestyle modifications may allow for deferment of invasive interventions and antiplatelet medications in PWH with symptomatic CAD, especially those with inhibitors. 78 Whether the benefits of low-dose aspirin prophylaxis for cardiovascular events outweigh the potential risk for bleeding in PWH is uncertain.…”
Section: General Principles In the Management Of Cardiovascular Diseamentioning
confidence: 99%
“…Some studies have reported lower mortality from CV diseases and/or decreased atherogenesis in patients with hemophilia because of the potentially protective effect of chronically low factor VIII (FVIII) activity on thrombus formation 2, 3. Conversely, other reports indicate comparable or higher CV comorbidities in patients with hemophilia compared with the general population 4, 5, 6. One such study specifically assessed the CV risk profile (via QRISK®2) of 709 patients aged ≥30 years in the Netherlands or United Kingdom 5.…”
Section: Tablementioning
confidence: 99%